2016
DOI: 10.1002/gps.4604
|View full text |Cite
|
Sign up to set email alerts
|

The correlates of anxiety among older adults in nursing homes and other residential aged care facilities: a systematic review

Abstract: While several variables were found to have strong associations with anxiety in aged care residents, a number of factors have been examined by only one or two studies. Further research (preferably prospective studies) is therefore needed to reliably confirm findings and to help plan and develop preventative and intervention strategies. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 57 publications
2
50
0
3
Order By: Relevance
“…Covariates that significantly contributed to the primary statistical model included age, sex, education, and smoking status, although they did not have a large influence on the magnitude of the association between physical activity and anxiety. Supporting previous findings, younger age, female sex, lower education, and smoking were significantly associated with increased likelihood of anxiety [73,74]. From the present analyses, potentially modifiable factors such as physical activity and smoking should be considered when designing interventions, while nonmodifiable factors such as age, sex, and education should be considered when identifying individuals who may be at increased risk of anxiety.…”
Section: Walkingsupporting
confidence: 85%
“…Covariates that significantly contributed to the primary statistical model included age, sex, education, and smoking status, although they did not have a large influence on the magnitude of the association between physical activity and anxiety. Supporting previous findings, younger age, female sex, lower education, and smoking were significantly associated with increased likelihood of anxiety [73,74]. From the present analyses, potentially modifiable factors such as physical activity and smoking should be considered when designing interventions, while nonmodifiable factors such as age, sex, and education should be considered when identifying individuals who may be at increased risk of anxiety.…”
Section: Walkingsupporting
confidence: 85%
“…According to Cohen, anxiety may also occur when a person with severe dementia experiences a lack of engagement with people or the environment, described as the "isolation anxiety of Alzheimer's disease" (Cohen, 1998). Studies have reported that unmet psychological and social needs of people with dementia in residential care, such as lack of social company, poor patient-caregiver relationship, and lack of daytime activity, are associated with anxiety symptoms (Creighton, Davison, & Kissane, 2017;Hancock, Woods, Challis, & Orrell, 2006). These situations can be prevented or minimized by nursing interventions, such as being with the patient, listening to music, going for a walk or outdoor activity, and engagement in social activities in small groups or one-on-one according to the person's preferences.…”
Section: Tractable Factorsmentioning
confidence: 99%
“…This section of the thesis highlights the studies that have investigated an association of anxiety with demographic, clinical, and psychosocial factors of people with dementia, and in a way is an extension of Section 2.5 of this thesis. To our knowledge, the earliest review examining the correlates of anxiety among residents (aged ≥ 50 years) of various long-term care is an Australian review that included 34 studies (Creighton et al, 2017). Thirty studies utilized cross-sectional designs, only six of which included participants with dementia.…”
Section: The Correlatesmentioning
confidence: 99%
“…Anxiety is a common psychiatric condition in older people, at a prevalence up to 15% [1,2]. With a lifetime prevalence of 29%, anxiety usually presents initially during youth [3].…”
Section: Introductionmentioning
confidence: 99%